1989
DOI: 10.1152/ajpregu.1989.256.5.r1063
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous opioids in the cardiovascular responses to asphyxia in fetal sheep

Abstract: Intravenous administration of the opioid receptor antagonist naloxone to asphyxiated fetal sheep increases the arterial blood pressure. We examined the hypothesis that endogenous opioids modify the cardiac output distribution during asphyxia due to changes in the vascular resistance of some fetal organs. Thirteen fetal sheep (0.8-0.9 of gestation) were chronically catheterized. Fetal asphyxia was induced by reducing the uterine blood flow with an inflatable occluder around the common internal iliac artery to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…It is clear that the fetal adrenal me dulla secretes catecholamines during fetal hypoxaemia and asphyxia [22,23] and we have also shown that the plasma concentrations of MERF are also significantly in creased during periods of fetal asphyxia associated with acute reductions in uterine blood flow [10]. Furthermore, it has been demonstrated that extra-and/or intra-adrenal opioid peptides play a key role in the fetal cardiovascular response to asphyxia and delivery [24,25], During birth or periods of reduced uterine blood flow, naloxone ad ministration to the fetal sheep results in an increase in fetal heart rate and blood pressure and a decrease in blood flow to the fetal kidneys and carcass. This suggests that during asphyxia, intra-or extra-adrenal opioids act to inhibit the catecholamine-induced vasoconstriction of these vascular beds [24], The source and identity of these opioid peptides remain to be established.…”
Section: Discussionmentioning
confidence: 95%
“…It is clear that the fetal adrenal me dulla secretes catecholamines during fetal hypoxaemia and asphyxia [22,23] and we have also shown that the plasma concentrations of MERF are also significantly in creased during periods of fetal asphyxia associated with acute reductions in uterine blood flow [10]. Furthermore, it has been demonstrated that extra-and/or intra-adrenal opioid peptides play a key role in the fetal cardiovascular response to asphyxia and delivery [24,25], During birth or periods of reduced uterine blood flow, naloxone ad ministration to the fetal sheep results in an increase in fetal heart rate and blood pressure and a decrease in blood flow to the fetal kidneys and carcass. This suggests that during asphyxia, intra-or extra-adrenal opioids act to inhibit the catecholamine-induced vasoconstriction of these vascular beds [24], The source and identity of these opioid peptides remain to be established.…”
Section: Discussionmentioning
confidence: 95%
“…Many reports have indicated that hypoxia may cause cerebrospinal fluid or plasma levels of β‐endorphin‐like immunoreactivity to increase. This is associated with respiratory difficulties, inhibits vasoconstriction and plays a role in the pathophysiology of prolonged infant apnea (14–17). It has been postulated that asphyxial cardiac arrest may cause a similar reaction in the body, and lead to the release of endogenous opiates that are partially responsible for respiratory, cardiac and peripheral vascular depression.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma renin and angiotensin II concentrations are high in the fetus compared to the non-pregnant ewe 72 and are thought to produce a tonic vasoconstriction, maintaining umbilical blood flow and gas exchange between the fetal and maternal circulations. 87 - 88 Whilst ANF has been shown to be increased in hypoxaemia 89 -90 little is known about its possible effects on the fetal circulation. Furthermore, infusion of angiotensin II into the fetal circulation produces a peripheral vasoconstriction.…”
Section: Cardiovascular Responses To Acute Isocapnic Hypoxaemiamentioning
confidence: 99%